Intrinsic Responses to Nitrogen Deficiency of Antarctic Ecotypes of Colobanthus Quitensis (Kunth) Bartl. and Deschampsia Antarctica Desv. - Zuniga-Navarro, G; Contreras-Arredondo, R (Elsevier Ireland Ltd, 2026)
Antarctic vascular plants Colobanthus quitensis and Deschampsia antarctica provide unique models for studying intrinsic adaptive responses to nutrient limitation, yet their responses to nitrogen deficiency remain poorly understood. Here, we investigated their ecophysiological adjustments under controlled axenic hydroponic conditions. After 15 days of nitrogen deprivation, both species exhibited pronounced root elongation, reflecting an adaptive shift to enhance nutrient acquisition. Nitrogen stress elevated reactive oxygen species (ROS) but did not increase malondialdehyde (MDA), indicating effective activation of antioxidant defenses. Enzyme assays revealed tissue-specific and enzyme-specific regulation: nitrate reductase (NR), nitrite reductase (NiR), and glutamate synthases (Fd-GOGAT, NADH-GOGAT) were generally downregulated, while glutamate dehydrogenase isoforms (NADPH-GDH, NADH-GDH) increased, particularly in older tissues, suggesting active nitrogen remobilization. Reduced phenylalanine ammonia-lyase (PAL) activity and total phenolic content highlighted a trade-off, diverting nitrogen from secondary metabolism to sustain primary functions. Altogether, these findings provide a comprehensive view of intrinsic strategies for nitrogen stress tolerance in Antarctic plants and offer translational insights for breeding crops with improved nitrogen use efficiency and resilience to climate-induced nutrient limitations. © 2025 Elsevier B.V.